Integron Analysis of Multidrug-Resistant Diarrheagenic E. coli Isolates from Travelers in Thailand - Ruksasiri, Supaporn; Bodhidatta, Ladaporn; Serichantalergs, Oralak; J. Mason, Carl; Tribuddharat, Chanwit (Naresuan University Journal: Science and Technology (NUJST), 2016)
Multidrug resistant (MDR) diarrheagenic Escherichia coli (DEC) is an important agent of traveler’s diarrhea. However, the reports on genetic mechanism conferring antimicrobial resistance among MDR-DEC of travelers in Thailand are limited. The aim of this study was to determine the prevalence and characterization of class 1 integrons among 49 MDR-DEC isolates from international travelers in Thailand in 2001-2004 and 2010. The majority (85%) of the isolates exhibited resistance to tetracycline, sulfisoxazole, ampicillin, streptomycin, and trimethoprim/sulfamethoxazole in both travelers with diarrhea and non- diarrhea. The most frequent phenotype was resistant to ampicillin-streptomycin-sulfisoxazole-trimethoprim/sulfamethoxazole-tetracycline. Using PCR specific primers to class 1 integrase ( intI1 ) gene, 5′- and 3′-conserved sequences (5′CS-3′CS), and dot-blot hybridization, 37 (75.5%) isolates harbored class 1 integrons, which were high prevalent in both of isolates from diarrhea and non-diarrhea groups. Resistance gene cassettes identified in this study were aadA1 and aadA2 (for streptomycin resistance) and linF (for lincosamide resistance). The presence of class 1 integrons carrying aadA2-linF is described for the first time from clinical sample in Thailand. This study emphasized an important role of class 1 integrons dissemination among community acquired MDR-DEC isolates in Thailand during the past 10 years and suggested the circulation of these resistance elements in this community. Therefore, further studies of the genetic and epidemiology of these organisms will be relevant for public health to limit the emergence of bacterial resistance. Keywords : Multidrug resistant (MDR), Diarrheagenic Escherichia coli (DEC), Integron, Resistance gene cassette
Keywords: Multidrug resistant (MDR), Diarrheagenic Escherichia coli (DEC), Integron, Resistance gene cassette